Does Early Marriage Make Women Happy?: A Phenomenological Finding from Madurese Women - Yudho Bawono; Suryanto Suryanto (Journal of Educational, Health and Community Psychology, 2019)
AbstractResearch on marriage has been pretty much done, including research on early marriage, particularly in Madura. Research on early marriage in Madura is exciting to do because this kind of marriage backed by a keen understanding of Islam, that if a child who is consider baligh (grown up) means they can be married. Madurese people believe in matchmaking as well as the existence of a belief, called sangkal (if the women reject the proposal from the male then the woman will be an old maid or ta’ paju lake’). This study aims to describe the happiness of Madurese women who married early in achieving, using a qualitative method with phenomenological approach. Research participants are Madurese women who are married under the age of 18, live in Madura, and are willing to be involved in research. Data collection used semi-structured interviews. The results of this study indicated that women from Madura can achieve happiness in their early marriage. This finding is different from other studies that found the occurrence of problems in the early marriage.